Free Legal Aid System: Legislation, Practice and Development Prospects (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article emphasizes that issues related to the system of providing free legal aid to the population are an important mechanism in the formation of a legal state and civil society, and analyzes opinions on its legal foundations and forms. Proposals and recommendations on the prospects for the development of this system are also provided.